Knowledge, Attitude, and Practice on Pediatric Tuberculosis Management among Healthcare Workers in the Centre Region of Cameroon: A Cross-Sectional Study. (15th December 2022) - Vukugah, Thomas Achombwom; Akoku, Derick Akompab; Tchoupa, Micheline Mekemnang; Lambert, Edward
Abstract : Background . This study was designed to assess the level of knowledge, attitude, and practice (KAP) of healthcare workers (HCWs) on pediatric TB management and its associated factors in the Centre Region of Cameroon. Methods . A cross-sectional study was conducted between January and March 2022. HCWs, selected through a multistage sampling technique in 21 health facilities, were interviewed using a KAP questionnaire on pediatric TB management. Logistic regression analyses were used to test associations between HCWs' characteristics and knowledge, attitudes, and practice levels at a 0.05 level of significance. Results . The median age of the participants was 35 years (IQR = 30–42), and the majority (73.2%) were females. About half (50.9%) of the participants (173/340) had good knowledge, 55.6% (189/340) had a good attitude, and 57.1% (194/340) had good practice scores on pediatric TB management. Having a bachelor's degree and above, working in the TB unit, and having received training on pediatric TB in the last five years were significantly associated with good knowledge of pediatric TB management. Similarly, having a bachelor's degree or higher and more than five years of experience providing TB services were significantly associated with a good attitude towards pediatric TB management. Being a general practitioner, nurse, and lab technician was significantly associated with good practice in pediatric TB management. Conclusion . The level of knowledge, attitude, and practice on pediatric TB management among HCWs was suboptimal, as substantial gaps were identified. The Ministry of Health and other international organizations need to prioritize training, coaching, and mentoring support to help HCWs improve their knowledge, attitude, and practice to detect, diagnose, and treat pediatric TB.